Investigation of Milk and Alternatives Intake and the Impact of School Nutrition Programs in First Nations Schoolchildren - Gates, Michelle (University of Waterloo, 2010)
Objectives: To assess the intake of milk and alternatives, calcium, and vitamin D in on-reserve First Nations youth in Ontario, Canada; and the relationship of these nutrients to body mass index. To assess the impact of a simple food provision program on the intakes of milk and alternatives among First Nations youth in Kashechewan First Nation and Attawapiskat First Nation, Ontario, Canada. To assess the process of implementing a comprehensive school nutrition education program, as well as its effects on the intake of milk and alternatives, as well as knowledge, intentions, and self-efficacy among First Nations youth in Fort Albany First Nation, Ontario. Methods: Twenty-four hour diet recall data collected by web-based survey between November 2003 and June 2010 (including pre- and post-program) were used to assess intakes. Milk and alternatives, calcium, and vitamin D intakes were described and compared to food and nutrition standards and to intakes in the general population (CCHS cycle 2.2), and related to BMI. Data collected in different years for the same community and season were used to assess yearly effects on milk and alternatives intake (four communities). Data collected in the same year and season but from different communities were used to assess latitudinal effects on milk and alternatives intake (four community pairs). Paired change in intakes was evaluated one week-post snack program implementation in Kashechewan and Attawapiskat, as well as one year post-program in Kashechewan. Change in intakes as well as knowledge, self-efficacy, and intentions were evaluated in Fort Albany after the completion of a comprehensive school-based program. Student (grades 6-8), teacher (from grades K-8), and parent impressions were collected via questionnaires and focus groups. Results: Mean intakes of milk and alternatives, calcium, and vitamin D were below recommendations and levels seen in the general population. No relationship between body mass index and milk and alternatives, calcium, or vitamin D intake was ...